The Students’ Character Strengthening by Using SMART-Based in Welcoming the 21st Century’s Learning - Octa Pratama Putra; Endry Boeriswati; Ratna Dewanti (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Both seeing and recognizing the crisis of moral values and character of students at the present time, absolutely, it becomes very important thing toward the educator. For instance, this happens to students entirely or partly at a certain school. In the future, it is expected to be a hope of the nation in leading the country. This research belongs to literature study. It means, it reviews of several sources of electronic books, electronic journals, and other references in supporting this article. Based on the results of the literature study, it can be concluded that character education needs to be strengthening by using SMART-based. SMART stand for: Setting-goal, Mannerly, Active, Respectful, and Thankful. So, the 21st century skills-based learning models used in the learning process as an effort to build the character of the student, of course, it is aligned to the needs and goals of learning. Then, the learning objectives can be done optimally. Thus, one of the goals of national education is the development of students’ character. Keywords: characters’ strengthening education, 21st century’s learning, and SMART